Profil Penderita Diare Anak Di Puskesmas Rawat Inap Pekanbaru - Esy Maryanti; Suri Dwi Lesmana; Hendro Mandela; Setri Herlina (Fakultas Kedokteran Universitas Riau, 2014)
Diarrhea is one of the most frequent diseases of infants and children in the world. In developing countries, diarrheais still one of the major causes of morbidity and mortality in children. In 2009, the incidence of diarrhea in childrenin Pekanbaru there were more than 5-6 people per day. Pekanbaru is the densely populated city that is very easyoccurrence of diarrhea in children. Many factors affect the incidence of diarrhea in children, one of which is theenvironment, hygiene and nutritional status of children. This study aims to determined the profile of children withdiarrhea in Health Centers Inpatient Pekanbaru. A total of 96 patients of diarrhea in children Pekanbaru HealthCenter Inpatient obtained most of the male sex (54.2%), with the age of majority was especially toddlers aged 1-3years. Nutritional status in patients with diarrhea was generally a good. Stool characteristics in childhood diarrheapatients was mostly mushy, not slimy and does not bleed.